Pre-transplant hypomethylating agents do not influence post-transplant survival in myelodysplastic syndrome. Issue 11 (19th September 2019) - Modi, Dipenkumar; Kim, Seongho; Singh, Vijendra; Ayash, Lois; Alavi, Asif; Ratanatharathorn, Voravit; Uberti, Joseph P.; Deol, Abhinav
Abstract: Information on the use of hypomethylating agents (HMAs) as a pre-transplant cytoreductive therapy in MDS is limited. We retrospectively evaluated outcomes of 172 adult MDS patients, who underwent allogeneic hematopoietic stem cell transplantation between January 2000 and December 2016. Patients were divided into three groups: group 1 – pre-transplant blasts <5% with HMA ( n = 42), group 2 – pre-transplant blasts ≥5% with HMA ( n = 38), group 3 – no HMA ( n = 92). With a median follow up of 4.08 years, 1-year survival and relapse rates for groups 1, 2, and 3 were 75%, 40.2%, and 60.71%, respectively; and 17.6%, 26.6%, and 9.8%, respectively. Multivariate analysis revealed adverse relapse (HR 3.54; p = .03) in group 2 compared to groups 1 and 3, while no difference in overall survival was noticed. Our study shows no survival association with pre-transplant HMA; although, higher relapse rate was observed in the non-responding patients indicating possible chemotherapy resistant disease.